Uploaded by Fritz Canaway

Differential Equations Lecture Notes

advertisement
University of Science and Technology of Southern Philippines
College of Engineering and Architecture
Electrical Engineering Department
ES 208 DIFFERENTIAL EQUATIONS
Julius A. Nacional Jr.
Instructor - 1a
𝑑𝑦
𝑦′ =
𝑑π‘₯
Prime Notation
𝑑2𝑦
𝑑𝑦
+
5
𝑑π‘₯ 2
𝑑π‘₯
π‘₯3
2𝑦
𝑑
𝑦 ′′ = 2
𝑑π‘₯
− 4𝑦 = 𝑒 π‘₯
𝑑2𝑦
𝑑𝑦
1−π‘₯
−
4π‘₯
+ 5𝑦 = cos π‘₯
𝑑π‘₯ 2
𝑑π‘₯
π‘₯5
2
𝑑𝑦
+
𝑑π‘₯
4
+𝑦=0
𝑑4𝑦
𝑑2𝑦
3
− 2π‘₯
+ 6𝑦 = 0
𝑑π‘₯ 4
𝑑π‘₯ 2
𝑑2𝑦
=
𝑑π‘₯ 2
𝑛
𝑦
𝑑𝑛 𝑦
= 𝑛
𝑑π‘₯
3
𝑑3𝑦
𝑑𝑦
2π‘₯
+
π‘₯
−
5𝑦
=
3𝑒
𝑑π‘₯ 3
𝑑π‘₯
𝑑3𝑦
π‘₯
𝑑π‘₯ 3
𝑦 ′′′
𝑑3𝑦
= 3
𝑑π‘₯
𝑑𝑦
1+
𝑑π‘₯
𝑦 ′′ + 5 𝑦′
3
− 4𝑦 = 𝑒 π‘₯
π‘₯ 3 𝑦′′′ + π‘₯𝑦′ − 5𝑦 = 3𝑒 2π‘₯
1 − π‘₯ 𝑦′′ − 4π‘₯𝑦′ + 5𝑦 = cos π‘₯
π‘₯ 𝑦′′′
π‘₯ 5𝑦
4
2
+ 𝑦′
4
+𝑦=0
− 2π‘₯ 3 𝑦′′ + 6𝑦 = 0
4
𝑦′′ =
1 + 𝑦′
4
𝑑𝑦
𝑦=
𝑑𝑑
Dot Notation
𝑑2𝑦
𝑑𝑦
+
5
𝑑𝑑 2
𝑑𝑑
𝑑2π‘₯
π‘₯= 2
𝑑𝑑
3
− 4𝑦 = 𝑒 𝑑
3
𝑑
π‘₯
𝑑π‘₯
𝑑3 3 + 𝑑
− 5π‘₯ = 3𝑒 2𝑑
𝑑𝑑
𝑑𝑑
𝑑2 𝑠
𝑑𝑠
1−𝑑
−
4𝑑
+ 5𝑠 = cos πœ”π‘‘
𝑑𝑑 2
𝑑𝑑
𝑑3𝑒
𝑑
𝑑𝑑 3
𝑑2𝑣
=
𝑑𝑣 2
2
𝑑3𝑠
𝑠= 3
𝑑𝑑
𝑑𝑒
+
𝑑𝑑
𝑑𝑣
1+
𝑑𝑑
𝑦+5 𝑦
3
− 4𝑦 = 𝑒 𝑑
𝑑 3 π‘₯ + 𝑑 π‘₯ − 5π‘₯ = 3𝑒 2𝑑
1 − 𝑑 𝑠 − 4𝑑𝑠 + 5𝑠 = cos πœ”π‘‘
4
+𝑒 =0
π‘₯ 𝑒
2
+ 𝑒
4
+𝑒 =0
4
𝑣=
1+ 𝑣
4
Subscript Notation (partial derivatives)
πœ•2𝑒 πœ•2𝑒
+
=0
πœ•π‘₯ 2 πœ•π‘¦ 2
𝑒π‘₯π‘₯ + 𝑒𝑦𝑦 = 0
πœ•2𝑒 πœ•2𝑒
πœ•π‘’
=
−2
πœ•π‘₯ 2 πœ•π‘‘ 2
πœ•π‘‘
𝑒π‘₯π‘₯ = 𝑒𝑑𝑑 − 2𝑒𝑑
πœ•π‘’
πœ•π‘£
=−
πœ•π‘¦
πœ•π‘₯
𝑒𝑦 = −𝑣π‘₯
Classification by Linearity
An nth order Ordinary Differential Equation (ODE) is linear when
𝑑𝑛 𝑦
𝑑 𝑛−1 𝑦
𝑑𝑦
π‘Žπ‘› π‘₯
+
π‘Ž
π‘₯
+
β‹―
+
π‘Ž
π‘₯
+ π‘Ž0 π‘₯ 𝑦 = 𝑔 π‘₯
𝑛−1
1
𝑑π‘₯ 𝑛
𝑑π‘₯ 𝑛−1
𝑑π‘₯
π‘Žπ‘› π‘₯ 𝑦
𝑛
+ π‘Žπ‘›−1 π‘₯ 𝑦
𝑛−1
+ β‹― + π‘Ž1 π‘₯ 𝑦′ + π‘Ž0 π‘₯ 𝑦 = 𝑔 π‘₯
where
 The dependent variable 𝑦 and all its derivatives 𝑦 ′ , 𝑦 ′′ , … , 𝑦 𝑛 are
of the first degree, the power of each term involving 𝑦 is 1.
 The coefficients π‘Ž0 , π‘Ž1 , … , π‘Žπ‘› of 𝑦 ′ , 𝑦 ′′ , … , 𝑦 𝑛 depend at most on
the independent variable x.
A non-linear ODE is simply one that is not linear.
𝑑2𝑦
𝑑𝑦
+
5
𝑑π‘₯ 2
𝑑π‘₯
3
− 4𝑦 = 𝑒 π‘₯
𝑑3𝑦
𝑑𝑦
2π‘₯
π‘₯
+
π‘₯
−
5𝑦
=
3𝑒
𝑑π‘₯ 3
𝑑π‘₯
Non-linear
3
Linear
𝑑2𝑦
𝑑𝑦
1−π‘₯
−
4π‘₯
+ 5𝑦 = cos π‘₯
𝑑π‘₯ 2
𝑑π‘₯
Linear
1 − 𝑦 𝑦 ′ + 2𝑦 = 𝑒 π‘₯
Non-linear
𝑑5
𝑑4𝑦
𝑑2𝑦
3
− 2𝑑
+ 6𝑦 = 0
𝑑𝑑 4
𝑑𝑑 2
𝑑2𝑦
+ sin 𝑦 = 0
𝑑π‘₯ 2
Linear
Non-linear
𝑑𝑛 𝑦
𝑑 𝑛−1 𝑦
𝑑𝑦
π‘Žπ‘› π‘₯
+
π‘Ž
π‘₯
+
β‹―
+
π‘Ž
π‘₯
+ π‘Ž0 π‘₯ 𝑦 = 𝑔 π‘₯
𝑛−1
1
𝑑π‘₯ 𝑛
𝑑π‘₯ 𝑛−1
𝑑π‘₯
𝑛=1
𝑑𝑦
π‘Ž1 π‘₯
+ π‘Ž0 π‘₯ 𝑦 = 𝑔 π‘₯
𝑑π‘₯
𝑛=2
𝑑2𝑦
𝑑𝑦
π‘Ž2 π‘₯
+ π‘Ž1 π‘₯
+ π‘Ž0 π‘₯ 𝑦 = 𝑔 π‘₯
𝑑π‘₯ 2
𝑑π‘₯
Solution of Ordinary Differential Equation
Any function φ, defined on an interval I and possessing at least n derivatives
that are continuous in I, which when substituted into an nth-order ordinary
differential equation reduces the equation to an identity, is said to be a
solution of the equation on the interval.
The solution of an nth-order ODE
𝐹 π‘₯, 𝑦, 𝑦 ′ , … , 𝑦
𝑛
=0
Is a function φ that possesses at least n derivatives and for which
𝐹 π‘₯, πœ‘ π‘₯ , πœ‘′ π‘₯ , … , πœ‘
𝑛
π‘₯
=0
for all x in I.
Example
Verify that the indicated function is a solution of the given differential
equation on the interval −∞, ∞ .
1
𝑑𝑦
1 4
a. 𝑑π‘₯ = π‘₯𝑦 2 ; 𝑦 = 16
π‘₯
b. 𝑦 ′′ − 2𝑦 ′ + 𝑦 = 0 ; 𝑦 = π‘₯𝑒 π‘₯
Solution:
a)
𝑑𝑦
1
= 16
𝑑π‘₯
1 4
𝑦 = 16
π‘₯
4π‘₯ 3
= 14π‘₯ 3
Substituting to the differential equation
𝑑𝑦
1
= π‘₯𝑦 2
𝑑π‘₯
1 3
4π‘₯
=π‘₯
1 4
16π‘₯
1
2
=π‘₯
1 2
4π‘₯
1 3
= π‘₯
4
b)
𝑦 = π‘₯𝑒 π‘₯
𝑦 ′ = π‘₯𝑒 π‘₯ + 𝑒 π‘₯
𝑦 ′′ = π‘₯𝑒 π‘₯ + 𝑒 π‘₯ + 𝑒 π‘₯ = π‘₯𝑒 π‘₯ + 2𝑒 π‘₯
Substituting to the differential equation
𝑦 ′′ − 2𝑦 ′ + 𝑦 = 0
π‘₯𝑒 π‘₯ + 2𝑒 π‘₯ − 2 π‘₯𝑒 π‘₯ + 𝑒 π‘₯ + π‘₯𝑒 π‘₯ = 0
0=0
Example
Verify that the indicated family of function 𝑦 = 𝑐1 π‘₯ −1 + 𝑐2 π‘₯ + 𝑐3 π‘₯ ln π‘₯ + 4π‘₯ 2
3
𝑑 𝑦
equation π‘₯ 3 𝑑π‘₯ 3
2
𝑑 𝑦
2π‘₯ 2 𝑑π‘₯ 2
𝑑𝑦
is a solution of the differential
+
− π‘₯ 𝑑π‘₯ + 𝑦 = 12π‘₯ 2 .
Assume an appropriate interval I of definition and 𝑐1 , 𝑐2 and 𝑐3 are arbitrary
constants or parameters.
Solution:
𝑦 = 𝑐1 π‘₯ −1 + 𝑐2 π‘₯ + 𝑐3 π‘₯ ln π‘₯ + 4π‘₯ 2
𝑑𝑦
1
−2
= 𝑐1 −π‘₯
+ 𝑐2 + 𝑐3 π‘₯
+ ln π‘₯ + 8π‘₯ = −𝑐1 π‘₯ −2 + 𝑐2 + 𝑐3 +𝑐3 ln π‘₯ +8x
𝑑π‘₯
π‘₯
𝑑2𝑦
−3 +𝑐 π‘₯ −1 +8
=
2𝑐
π‘₯
1
3
𝑑π‘₯ 2
𝑑3𝑦
= −6𝑐1 π‘₯ −4 − 𝑐3 π‘₯ −2
3
𝑑π‘₯
Substituting to the differential equation
π‘₯3
𝑑3𝑦
𝑑2𝑦
𝑑𝑦
2
+ 2π‘₯
−π‘₯
+ 𝑦 = 12π‘₯ 2
3
2
𝑑π‘₯
𝑑π‘₯
𝑑π‘₯
𝑑3𝑦
3
−4
−2
−1
π‘₯
=
π‘₯
−6𝑐
π‘₯
−
𝑐
π‘₯
=
−6𝑐
π‘₯
− 𝑐3 π‘₯
1
3
1
𝑑π‘₯ 3
3
𝑑2𝑦
2
−3
−1
−1
2
2π‘₯
=
2π‘₯
2𝑐
π‘₯
+𝑐
π‘₯
+8
=
4𝑐
π‘₯
+2𝑐
π‘₯+16π‘₯
1
3
1
3
𝑑π‘₯ 2
2
𝑑𝑦
−π‘₯
= −π‘₯ −𝑐1 π‘₯ −2 + 𝑐2 + 𝑐3 +𝑐3 ln π‘₯ +8x = 𝑐1 π‘₯ −1 − 𝑐2 π‘₯ − 𝑐3 π‘₯ − 𝑐3 π‘₯ ln π‘₯ −8π‘₯ 2
𝑑π‘₯
𝑦 = 𝑐1 π‘₯ −1 + 𝑐2 π‘₯ + 𝑐3 π‘₯ ln π‘₯ + 4π‘₯ 2
12π‘₯ 2 = 12π‘₯ 2
Example
Verify that the indicated pair of functions
π‘₯ = cos 2𝑑 + sin 2𝑑 + 15𝑒 𝑑
𝑦 = − cos 2𝑑 − sin 2𝑑 − 15𝑒 𝑑
is a solution of the system of differential equations
𝑑2 π‘₯
𝑑𝑑 2
𝑑2 𝑦
𝑑𝑑 2
= 4𝑦 + 𝑒 𝑑
= 4π‘₯ − 𝑒 𝑑
on the interval −∞, ∞ .
Solution:
π‘₯ = cos 2𝑑 + sin 2𝑑 + 15𝑒 𝑑
𝑦 = −cos 2𝑑 − sin 2𝑑 − 15𝑒 𝑑
𝑑π‘₯
= −2 sin 2𝑑 + 2 cos 2𝑑 + 15𝑒 𝑑
𝑑𝑑
𝑑𝑦
= 2 sin 2𝑑 − 2 cos 2𝑑 − 15𝑒 𝑑
𝑑𝑑
𝑑2π‘₯
= −4 cos 2𝑑 − 4 sin 2𝑑 + 15𝑒 𝑑
2
𝑑𝑑
𝑑2𝑦
1 𝑑
=
4
cos
2𝑑
+
4
sin
2𝑑
−
5𝑒
𝑑𝑑 2
Substituting to the differential equation
𝑑2π‘₯
= 4𝑦 + 𝑒 𝑑
2
𝑑𝑑
−4 cos 2𝑑 − 4 sin 2𝑑 + 15𝑒 𝑑 = 4 −cos 2𝑑 − sin 2𝑑 − 15𝑒 𝑑 + 𝑒 𝑑
= −4cos 2𝑑 − 4 sin 2𝑑 − 45𝑒 𝑑 + 𝑒 𝑑
−4 cos 2𝑑 − 4 sin 2𝑑 + 15𝑒 𝑑 = −4 cos 2𝑑 − 4 sin 2𝑑 + 15𝑒 𝑑
𝑑2𝑦
= 4π‘₯ − 𝑒 𝑑
2
𝑑𝑑
4 cos 2𝑑 + 4 sin 2𝑑 − 15𝑒 𝑑 = 4 cos 2𝑑 + sin 2𝑑 + 15𝑒 𝑑 − 𝑒 𝑑
= 4 cos 2𝑑 + 4 sin 2𝑑 + 45𝑒 𝑑 − 𝑒 𝑑
4 cos 2𝑑 + 4 sin 2𝑑 − 15𝑒 𝑑 = 4 cos 2𝑑 + 4 sin 2𝑑 − 15𝑒 𝑑
Example
Find the values of m so that the function
𝑦 = 𝑒 π‘šπ‘₯
is a solution of the differential equation
2𝑦 ′′ + 7𝑦 ′ − 4𝑦 = 0
Solution:
𝑦 = 𝑒 π‘šπ‘₯
𝑦′ = π‘šπ‘’ π‘šπ‘₯
𝑦′′ = π‘š2 𝑒 π‘šπ‘₯
Substituting to the differential equation
2𝑦 ′′ + 7𝑦 ′ − 4𝑦 = 0
2π‘š2 𝑒 π‘šπ‘₯ + 7π‘šπ‘’ π‘šπ‘₯ − 4𝑒 π‘šπ‘₯ = 0
2π‘š2 + 7π‘š − 4 𝑒 π‘šπ‘₯ = 0
2π‘š2 + 7π‘š − 4 = 0
2π‘š − 1 π‘š + 4 = 0
2π‘š − 1 = 0
π‘š=1 2
π‘š+4=0
π‘š = −4
Assignment #1
Exercises 1-19 of ref ii
Problems 1-13,15-20 of ref iv
Solution of Ordinary Differential Equation (ref I,pp 6)
Any function φ, defined on an interval I and possessing at least n derivatives
that are continuous in I, which when substituted into an nth-order ordinary
differential equation reduces the equation to an identity, is said to be a
solution of the equation on the interval.
The solution of an nth-order ODE
𝐹 π‘₯, 𝑦, 𝑦 ′ , … , 𝑦
𝑛
=0
Is a function φ that possesses at least n derivatives and for which
𝐹 π‘₯, πœ‘ π‘₯ , πœ‘′ π‘₯ , … , πœ‘
𝑛
π‘₯
=0
for all x in I.
Example (ref I, pp 7
Verify that the indicated function is a solution of the given differential
equation on the interval −∞, ∞ .
1
𝑑𝑦
1 4
a. 𝑑π‘₯ = π‘₯𝑦 2 ; 𝑦 = 16
π‘₯
Solution:
a)
𝑑𝑦
1
= 16
𝑑π‘₯
1 4
𝑦 = 16
π‘₯
4π‘₯ 3
= 14π‘₯ 3
Substituting to the differential equation
𝑑𝑦
1
= π‘₯𝑦 2
𝑑π‘₯
1 3
4π‘₯
=π‘₯
1 4
16π‘₯
1
2
=π‘₯
1 2
4π‘₯
1 3
= π‘₯
4
b)
𝑦 ′′ − 2𝑦 ′ + 𝑦 = 0 ; 𝑦 = π‘₯𝑒 π‘₯
𝑦 = π‘₯𝑒 π‘₯
𝑦 ′ = π‘₯𝑒 π‘₯ + 𝑒 π‘₯
𝑦 ′′ = π‘₯𝑒 π‘₯ + 𝑒 π‘₯ + 𝑒 π‘₯ = π‘₯𝑒 π‘₯ + 2𝑒 π‘₯
Substituting to the differential equation
𝑦 ′′ − 2𝑦 ′ + 𝑦 = 0
π‘₯𝑒 π‘₯ + 2𝑒 π‘₯ − 2 π‘₯𝑒 π‘₯ + 𝑒 π‘₯ + π‘₯𝑒 π‘₯ = 0
0=0
Example (ref i
Verify that the indicated family of function 𝑦 = 𝑐1 π‘₯ −1 + 𝑐2 π‘₯ + 𝑐3 π‘₯ ln π‘₯ + 4π‘₯ 2
3
𝑑 𝑦
equation π‘₯ 3 𝑑π‘₯ 3
2
𝑑 𝑦
2π‘₯ 2 𝑑π‘₯ 2
𝑑𝑦
is a solution of the differential
+
− π‘₯ 𝑑π‘₯ + 𝑦 = 12π‘₯ 2 .
Assume an appropriate interval I of definition and 𝑐1 , 𝑐2 and 𝑐3 are arbitrary
constants or parameters.
Solution:
𝑦 = 𝑐1 π‘₯ −1 + 𝑐2 π‘₯ + 𝑐3 π‘₯ ln π‘₯ + 4π‘₯ 2
𝑑𝑦
1
−2
= 𝑐1 −π‘₯
+ 𝑐2 + 𝑐3 π‘₯
+ ln π‘₯ + 8π‘₯ = −𝑐1 π‘₯ −2 + 𝑐2 + 𝑐3 +𝑐3 ln π‘₯ +8x
𝑑π‘₯
π‘₯
𝑑2𝑦
−3 +𝑐 π‘₯ −1 +8
=
2𝑐
π‘₯
1
3
𝑑π‘₯ 2
𝑑3𝑦
= −6𝑐1 π‘₯ −4 − 𝑐3 π‘₯ −2
3
𝑑π‘₯
Substituting to the differential equation
π‘₯3
𝑑3𝑦
𝑑2𝑦
𝑑𝑦
2
+ 2π‘₯
−π‘₯
+ 𝑦 = 12π‘₯ 2
3
2
𝑑π‘₯
𝑑π‘₯
𝑑π‘₯
𝑑3𝑦
3
−4
−2
−1
π‘₯
=
π‘₯
−6𝑐
π‘₯
−
𝑐
π‘₯
=
−6𝑐
π‘₯
− 𝑐3 π‘₯
1
3
1
𝑑π‘₯ 3
3
𝑑2𝑦
2
−3
−1
−1
2
2π‘₯
=
2π‘₯
2𝑐
π‘₯
+𝑐
π‘₯
+8
=
4𝑐
π‘₯
+2𝑐
π‘₯+16π‘₯
1
3
1
3
𝑑π‘₯ 2
2
𝑑𝑦
−π‘₯
= −π‘₯ −𝑐1 π‘₯ −2 + 𝑐2 + 𝑐3 +𝑐3 ln π‘₯ +8x = 𝑐1 π‘₯ −1 − 𝑐2 π‘₯ − 𝑐3 π‘₯ − 𝑐3 π‘₯ ln π‘₯ −8π‘₯ 2
𝑑π‘₯
𝑦 = 𝑐1 π‘₯ −1 + 𝑐2 π‘₯ + 𝑐3 π‘₯ ln π‘₯ + 4π‘₯ 2
12π‘₯ 2 = 12π‘₯ 2
Example
Verify that the indicated pair of functions
π‘₯ = cos 2𝑑 + sin 2𝑑 + 15𝑒 𝑑
𝑦 = − cos 2𝑑 − sin 2𝑑 − 15𝑒 𝑑
is a solution of the system of differential equations
𝑑2 π‘₯
𝑑𝑑 2
𝑑2 𝑦
𝑑𝑑 2
= 4𝑦 + 𝑒 𝑑
= 4π‘₯ − 𝑒 𝑑
on the interval −∞, ∞ .
Solution:
π‘₯ = cos 2𝑑 + sin 2𝑑 + 15𝑒 𝑑
𝑦 = −cos 2𝑑 − sin 2𝑑 − 15𝑒 𝑑
𝑑π‘₯
= −2 sin 2𝑑 + 2 cos 2𝑑 + 15𝑒 𝑑
𝑑𝑑
𝑑𝑦
= 2 sin 2𝑑 − 2 cos 2𝑑 − 15𝑒 𝑑
𝑑𝑑
𝑑2π‘₯
= −4 cos 2𝑑 − 4 sin 2𝑑 + 15𝑒 𝑑
2
𝑑𝑑
𝑑2𝑦
1 𝑑
=
4
cos
2𝑑
+
4
sin
2𝑑
−
5𝑒
𝑑𝑑 2
Substituting to the differential equation
𝑑2π‘₯
= 4𝑦 + 𝑒 𝑑
2
𝑑𝑑
−4 cos 2𝑑 − 4 sin 2𝑑 + 15𝑒 𝑑 = 4 −cos 2𝑑 − sin 2𝑑 − 15𝑒 𝑑 + 𝑒 𝑑
= −4cos 2𝑑 − 4 sin 2𝑑 − 45𝑒 𝑑 + 𝑒 𝑑
−4 cos 2𝑑 − 4 sin 2𝑑 + 15𝑒 𝑑 = −4 cos 2𝑑 − 4 sin 2𝑑 + 15𝑒 𝑑
𝑑2𝑦
= 4π‘₯ − 𝑒 𝑑
2
𝑑𝑑
4 cos 2𝑑 + 4 sin 2𝑑 − 15𝑒 𝑑 = 4 cos 2𝑑 + sin 2𝑑 + 15𝑒 𝑑 − 𝑒 𝑑
= 4 cos 2𝑑 + 4 sin 2𝑑 + 45𝑒 𝑑 − 𝑒 𝑑
4 cos 2𝑑 + 4 sin 2𝑑 − 15𝑒 𝑑 = 4 cos 2𝑑 + 4 sin 2𝑑 − 15𝑒 𝑑
Example
Find the values of m so that the function
𝑦 = 𝑒 π‘šπ‘₯
is a solution of the differential equation
2𝑦 ′′ + 7𝑦 ′ − 4𝑦 = 0
Solution:
𝑦 = 𝑒 π‘šπ‘₯
𝑦′ = π‘šπ‘’ π‘šπ‘₯
𝑦′′ = π‘š2 𝑒 π‘šπ‘₯
Substituting to the differential equation
2𝑦 ′′ + 7𝑦 ′ − 4𝑦 = 0
2π‘š2 𝑒 π‘šπ‘₯ + 7π‘šπ‘’ π‘šπ‘₯ − 4𝑒 π‘šπ‘₯ = 0
2π‘š2 + 7π‘š − 4 𝑒 π‘šπ‘₯ = 0
2π‘š2 + 7π‘š − 4 = 0
2π‘š − 1 π‘š + 4 = 0
2π‘š − 1 = 0
π‘š=1 2
π‘š+4=0
π‘š = −4
Assignment #1
Problems 1-13,15-28 of ref iv, pp 24-25
Problem Set #1
#s 1-29 of exercise 1.3 of ref i, pp 30-33
Deadline Sept. 21, 2022
𝑓𝐷 = 𝛾𝑣
𝑀 = π‘šπ‘”
𝐹 = 𝑀 − 𝑓𝐷 = π‘šπ‘” − 𝛾𝑣
𝐹 = π‘šπ‘Ž
π‘šπ‘Ž = π‘šπ‘” − 𝛾𝑣
π‘Ž=
π‘š
𝑑𝑣
𝑑𝑑
𝑑𝑣
= π‘šπ‘” − 𝛾𝑣
𝑑𝑑
𝑑𝑣
𝛾
=𝑔− 𝑣
𝑑𝑑
π‘š
𝑔 = 9.8 π‘š
𝑠2
𝑑𝑣
𝛾
= 9.8 − 𝑣
𝑑𝑑
π‘š
π‘š = 10 π‘˜π‘”
𝛾=2
𝑑𝑣
𝑣
= 9.8 −
𝑑𝑑
5
π‘˜π‘”
𝑠
𝑣 𝑑 =?
A first-order differential equation of the form
𝑑𝑦
=𝑔 π‘₯ β„Ž 𝑦
𝑑π‘₯
is said to be separable or to have separable variables.
𝑝 π‘₯, 𝑦 𝑑π‘₯ + π‘ž π‘₯, 𝑦 𝑑𝑦 = 0
r π‘₯ 𝑑π‘₯ + 𝑠 𝑦 𝑑𝑦 = 0
Example 1 ( ref ii pp 18)
Solution
𝑑𝑦
𝑑π‘₯
=2
𝑦
π‘₯
𝑑𝑦
𝑑π‘₯
= 2
𝑦
π‘₯
ln 𝑦 = 2 ln π‘₯ + 𝑐1
π‘Ž ln 𝑏 = ln π‘π‘Ž
ln 𝑦 = ln π‘₯ 2 + 𝑐1
𝑒 ln 𝑦 = 𝑒 ln π‘₯
2 +𝑐
1
2
𝑒 ln 𝑦 = 𝑒 ln π‘₯ 𝑒 𝑐1
𝑒 ln π‘Ž = π‘Ž
𝑦 = 𝑐π‘₯ 2
𝑒 𝑐1 = 𝑐
General Solution
Example 2 ( ref ii pp 20)
Solution
𝑑π‘₯
𝑑𝑦
+
=0
1 + π‘₯2 1 + 𝑦2
𝑑𝑒
1
𝑒
−1
=
tan
+𝑐
π‘Ž2 + 𝑒2 π‘Ž
π‘Ž
tan−1 π‘₯ + tan−1 𝑦 = 𝑐
General Solution
@ π‘₯ = 0, 𝑦 = −1
1
0− πœ‹ =𝑐
4
1
𝑐=− πœ‹
4
1
tan−1 π‘₯ + tan−1 𝑦 = − πœ‹
4
Particular Solution
Example 3 ( ref ii pp 22)
Solution
𝑦 𝑑𝑦
2π‘₯ 𝑑π‘₯ −
=0
𝑦+1
𝑦
1
=1−
𝑦+1
𝑦+1
2π‘₯ 𝑑π‘₯ − 1 −
2π‘₯ 𝑑π‘₯ −
1
𝑑𝑦 = 0
𝑦+1
1
1−
𝑑𝑦 = 𝑐
𝑦+1
π‘₯ 2 − 𝑦 + ln 𝑦 + 1 = 𝑐
@ π‘₯ = 0, 𝑦 = −2
2 + ln −1 = 𝑐
𝑐=2
π‘₯ 2 − 𝑦 + ln 𝑦 + 1 = 2
Example 4 ( ref iv pp 42)
Solution
1 − 𝑦 2 𝑑𝑦 = π‘₯ 2 𝑑π‘₯
1 3 1 3 𝑐
𝑦− 𝑦 = π‘₯ +
3
3
3
3𝑦 − 𝑦 3 = π‘₯ 3 + 𝑐
Example 5 ( ref iv pp 45)
Solution
2 𝑦 − 1 𝑑𝑦 = 3π‘₯ 2 + 4π‘₯ + 2 𝑑π‘₯
𝑦 2 − 2𝑦 = π‘₯ 3 + 2π‘₯ 2 + 2π‘₯ + 𝑐
@ π‘₯ = 0, 𝑦 = −1
1+2=𝑐
𝑦−1
= π‘₯ 3 + 2π‘₯ 2 + 2π‘₯ + 𝑐1
𝑦 2 − 2𝑦 + 1 = π‘₯ 3 + 2π‘₯ 2 + 2π‘₯ + 𝑐1
@ π‘₯ = 0, 𝑦 = −1
𝑐=3
𝑦 2 − 2𝑦 = π‘₯ 3 + 2π‘₯ 2 + 2π‘₯ + 3
2
1 + 2 + 1 = 𝑐1
𝑐1 = 4
𝑦 2 − 2𝑦 + 1 = π‘₯ 3 + 2π‘₯ 2 + 2π‘₯ + 4
𝑦 2 − 2𝑦 = π‘₯ 3 + 2π‘₯ 2 + 2π‘₯ + 3
Example 6 ( ref i pp 52)
Solve the differential equation
𝑑𝑦
2𝑦 + 3
=
𝑑π‘₯
4π‘₯ + 5
2
Solution
𝑑𝑦
2𝑦 + 3
=
𝑑π‘₯
4π‘₯ + 5
2𝑦 + 3
−
−2
2
2𝑦 + 3
=
4π‘₯ + 5
𝑑𝑦 = 4π‘₯ + 5
1
2𝑦 + 3
2
−1
=−
−2
2
2
𝑑π‘₯
1
4π‘₯ + 5
4
−1
−
𝑐
4
2 4π‘₯ + 5 = 2𝑦 + 3 + 𝑐 2𝑦 + 3 4π‘₯ + 5
8π‘₯ − 2𝑦 + 7 = 𝑐 8π‘₯𝑦 + 12π‘₯ + 10𝑦 + 15
Example 7 ( ref i pp 52)
Solve the differential equation
sin 3π‘₯ 𝑑π‘₯ + 2π‘¦π‘π‘œπ‘  3 3π‘₯ 𝑑𝑦 = 0
Solution
sin 3π‘₯ π‘π‘œπ‘  −3 3π‘₯ 𝑑π‘₯ + 2𝑦 𝑑𝑦 = 0
1
𝑐
π‘π‘œπ‘  −2 3π‘₯ + 𝑦 2 =
6
6
𝑠𝑒𝑐 2 3π‘₯ + 6𝑦 2 = 𝑐
Example 7 ( ref i pp 52)
Solve the differential equation
𝑑𝑦 π‘₯𝑦 + 2𝑦 − π‘₯ − 2
=
𝑑π‘₯ π‘₯𝑦 − 3𝑦 + π‘₯ − 3
Solution
π‘₯+2 𝑦−1
𝑑𝑦 π‘₯𝑦 + 2𝑦 − π‘₯ − 2 𝑦 π‘₯ + 2 − π‘₯ + 2
=
=
=
π‘₯−3 𝑦+1
𝑑π‘₯ π‘₯𝑦 − 3𝑦 + π‘₯ − 3 𝑦 π‘₯ − 3 + π‘₯ − 3
𝑦+1
π‘₯+2
𝑑𝑦 =
𝑑π‘₯
𝑦−1
π‘₯−3
2
1+
𝑑𝑦 =
𝑦−1
5
1+
𝑑π‘₯ + 𝑐
π‘₯−3
𝑦 + 2 ln 𝑦 − 1 = π‘₯ + 5 ln π‘₯ − 3 + 𝑐
Example 8 ( ref i pp 52)
Find the particular solution of the given initial-value problem
𝑒 2𝑦 − 𝑦 cos π‘₯
𝑑𝑦
= 𝑒 𝑦 sin 2π‘₯
𝑑π‘₯
𝑦 0 =0
Solution
𝑒 2𝑦 − 𝑦
sin 2π‘₯
𝑑𝑦
=
𝑑π‘₯
𝑒𝑦
cos π‘₯
sin 2πœƒ = 2 sin πœƒ cos πœƒ
𝑒 𝑦 − 𝑦𝑒 −𝑦 𝑑𝑦 =
𝑒 𝑑𝑣 = 𝑒𝑣 −
𝑣 𝑑𝑒
𝑒=𝑦
𝑑𝑣 = 𝑒 −𝑦 𝑑𝑦
𝑑𝑒 = 𝑑𝑦
𝑣 = −𝑒 −𝑦
2 sin π‘₯ 𝑑π‘₯ + 𝑐
𝑒 𝑦 − −𝑦𝑒 −𝑦 − 𝑒 −𝑦 = −2 cos π‘₯ + 𝑐
𝑒 𝑦 + 𝑦𝑒 −𝑦 + 𝑒 −𝑦 = −2 cos π‘₯ + 𝑐
@π‘₯ = 0, 𝑦 = 0
1 + 0 + 1 = −2 + 𝑐
𝑐=4
𝑒 𝑦 + 𝑦𝑒 −𝑦 + 𝑒 −𝑦 = 4 − 2 cos π‘₯
𝑦𝑒 −𝑦 𝑑𝑦 = −𝑦𝑒 −𝑦 +
𝑒 −𝑦 𝑑𝑦
𝑦𝑒 −𝑦 𝑑𝑦 = −𝑦𝑒 −𝑦 − 𝑒 −𝑦
Example 9 ( ref i pp 52)
Find the particular solution of the given initial-value problem
𝑑𝑦 𝑦 2 − 1
=
,𝑦 2 = 2
𝑑π‘₯ π‘₯ 2 − 1
Solution
𝑑𝑦
𝑑π‘₯
=
𝑦2 − 1 π‘₯2 − 1
1
1
1
1
−
𝑑𝑦 =
2
𝑦−1 𝑦+1
2
1
𝐴
𝐡
=
+
𝑒2 − 1 𝑒 + 1 𝑒 − 1
1
1
−
𝑑π‘₯ + 𝑐1
π‘₯−1 π‘₯+1
1=𝐴 𝑒−1 +𝐡 𝑒+1
@𝑒 =1
@ 𝑒 = −1
1
1
ln 𝑦 − 1 − ln 𝑦 + 1 = ln π‘₯ − 1 − ln π‘₯ + 1 + 𝑐1
2
2
𝐡 = 12
𝐴 = −12
1
𝑦−1
1
π‘₯−1
ln
= ln
+ 𝑐1
1
1
1
2
𝑦+1
2
π‘₯+1
2
2
=
−
𝑒2 − 1 𝑒 − 1 𝑒 + 1
𝑦−1
π‘₯−1
ln
− ln
= 2𝑐1
𝑦+1
π‘₯+1
π‘Ž
ln π‘Ž − ln 𝑏 = ln
𝑦−1
𝑏
𝑦−1 π‘₯+1
π‘₯𝑦 − π‘₯ + 𝑦 − 1
𝑦+1
ln
= ln
= ln
= 2𝑐1
π‘₯−1
𝑦+1 π‘₯−1
π‘₯𝑦 + π‘₯ − 𝑦 − 1
π‘₯+1
π‘₯𝑦 − π‘₯ + 𝑦 − 1
ln
= 2𝑐1
π‘₯𝑦 + π‘₯ − 𝑦 − 1
π‘₯𝑦 − π‘₯ + 𝑦 − 1
= 𝑒 2𝑐1 = 𝑐
π‘₯𝑦 + π‘₯ − 𝑦 − 1
π‘₯𝑦 − π‘₯ + 𝑦 − 1 = c π‘₯𝑦 + π‘₯ − 𝑦 − 1
@ π‘₯ = 2, 𝑦 = 2
4−2+2−1=c 4+2−2−1
𝑐=1
π‘₯𝑦 − π‘₯ + 𝑦 − 1 = π‘₯𝑦 + π‘₯ − 𝑦 − 1
2𝑦 = 2π‘₯
π’š=𝒙
𝑒 ln π‘Ž = π‘Ž
Assignment #2
Exercises 7-37 on pp. 23 of ref ii
Problems 1-28 on pp. 47- 49 of ref iv
𝑓 π‘₯, 𝑦 = π‘₯ 2 − 3π‘₯𝑦 + 4𝑦 2
𝑓 πœ†π‘₯, πœ†π‘¦ = πœ†π‘₯
2
− 3 πœ†π‘₯ πœ†π‘¦ + 4 πœ†π‘¦
𝑓 πœ†π‘₯, πœ†π‘¦ = πœ†2 π‘₯ 2 − 3πœ†2 π‘₯𝑦 + 4πœ†2 𝑦 2
𝑓 πœ†π‘₯, πœ†π‘¦ = πœ†2 π‘₯ 2 − 3π‘₯𝑦 + 4𝑦 2
𝑓 πœ†π‘₯, πœ†π‘¦ = πœ†2 𝑓 π‘₯, 𝑦
2
π‘₯
M and N are homogeneous of the same degree
π‘₯ = 𝑒𝑦
π‘œπ‘Ÿ
𝑦
𝑦
−1 𝑒
π‘₯
𝑦−π‘₯ 𝑒
𝑦
π‘₯
π‘₯
=𝑐
=𝑐
𝑦 = 𝑣π‘₯
Example 1 ( ref ii pp. 26)
Solution:
𝑦 = 𝑣π‘₯
π‘₯ 2 − π‘₯ 𝑣π‘₯ + 𝑣π‘₯
𝑑𝑦 = 𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣
2
𝑑π‘₯ − π‘₯ 𝑣π‘₯ 𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣 = 0
π‘₯ 2 1 − 𝑣 + 𝑣 2 𝑑π‘₯ − π‘₯ 2 𝑣 𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣 = 0
1 − 𝑣 + 𝑣 2 𝑑π‘₯ − 𝑣 𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣 = 0
1 − 𝑣 𝑑π‘₯ − 𝑣π‘₯ 𝑑𝑣 = 0
𝑑π‘₯ 𝑣 𝑑𝑣
−
=0
π‘₯
1−𝑣
𝑑π‘₯ 𝑣 𝑑𝑣
+
=0
π‘₯
𝑣−1
𝑑π‘₯
1
+ 1+
𝑑𝑣 = 0
π‘₯
𝑣−1
ln π‘₯ + 𝑣 + ln 𝑣 − 1 = 𝑐1
𝑒
ln π‘₯ +𝑣+ln 𝑣−1
π‘₯ 𝑣 − 1 𝑒𝑣 = 𝑐
= 𝑒 𝑐1
Example 1 ( ref ii pp. 26)
Solution:
π‘₯ = 𝑒𝑦
𝑒𝑦
2
𝑑π‘₯ = 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒
− 𝑒𝑦 𝑦 + 𝑦 2 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒 − 𝑒𝑦 𝑦 𝑑𝑦 = 0
𝑦 2 𝑒2 − 𝑒 + 1 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒 − 𝑦 2 𝑒 𝑑𝑦 = 0
𝑒2 − 𝑒 𝑒 𝑑𝑦 + 𝑦 𝑒2 − 𝑒 + 1 𝑑𝑒 = 0
𝑑𝑦
𝑒2 − 𝑒 + 1
+
𝑑𝑒 = 0
𝑦
𝑒2 𝑒 − 1
𝑑𝑦
1
1
+
− 2 𝑑𝑒 = 0
𝑦
𝑒−1 𝑒
1
ln 𝑦 + ln 𝑒 − 1 + = ln 𝑐
𝑒
𝑦 𝑒−1 𝑒
1
𝑒
π‘₯
𝑦
𝑦
−1 𝑒
𝑦
= 𝑐1
π‘₯
= 𝑐1
𝑒2 − 𝑒 + 1 𝐴 𝐡
𝐢
= + 2+
𝑒2 𝑒 − 1
𝑒 𝑒
𝑒−1
𝑒2 − 𝑒 + 1 = 𝐴 𝑒2 − 𝑒 + 𝐡 𝑒 − 1 + 𝐢𝑒2
𝐡 = −1
𝐡 − 𝐴 = −1
𝐴+𝐢 =1
π‘₯−𝑦 𝑒
𝐴=0
𝐢=1
𝑦
𝑦−π‘₯ 𝑒
𝑦
π‘₯
= 𝑐1
π‘₯
=𝑐
Example 2 ( ref ii pp. 27)
Solution:
π‘₯ = 𝑒𝑦
𝑑π‘₯ = 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒
2
𝑦2
𝑒𝑦 𝑦 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒 + 𝑒𝑦 +
𝑑𝑦 = 0
𝑒𝑦 2 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒 + 𝑦 2 𝑒2 + 1 𝑑𝑦 = 0
𝑒 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒 + 𝑒2 + 1 𝑑𝑦 = 0
𝑒𝑦 𝑑𝑒 + 2𝑒2 + 1 𝑑𝑦 = 0
𝑒 𝑑𝑒
𝑑𝑦
+
=0
2𝑒2 + 1 𝑦
1
1
ln 2𝑒2 + 1 + ln 𝑦 = ln 𝑐
4
4
ln 2𝑒2 + 1 + 4 ln 𝑦 = ln 𝑐
ln 2𝑒2 + 1 𝑦 4 = ln 𝑐
2𝑒2 + 1 𝑦 4 = 𝑐
π‘₯
2
𝑦
2
+ 1 𝑦4 = 𝑐
2π‘₯ 2 + 𝑦 2 𝑦 2 = 𝑐
Example 2 ( ref ii pp. 27)
Solution:
𝑦 = 𝑣π‘₯
𝑑𝑦 = 𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣
π‘₯ 𝑣π‘₯ 𝑑π‘₯ + π‘₯ 2 + 𝑣π‘₯
𝑣π‘₯ 2 𝑑π‘₯
π‘₯2
2
𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣 = 0
𝑣2
+
1+
𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣 = 0
𝑣𝑑π‘₯ + 1 + 𝑣 2 𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣 = 0
2𝑣 + 𝑣 3 𝑑π‘₯ + 1 + 𝑣 2 π‘₯ 𝑑𝑣 = 0
𝑑π‘₯
1 + 𝑣2
+
π‘₯
𝑣 2 + 𝑣2
1 + 𝑣2
𝐴
𝐡
2𝑣𝐢
=
+
+
𝑣 2 + 𝑣2
𝑣 2 + 𝑣2 2 + 𝑣2
𝑑𝑣 = 0
𝑑π‘₯
1 1
1
2𝑣
+
+
π‘₯
2 𝑣
4 2 + 𝑣2
𝑑𝑣 = 0
1
1
1
ln π‘₯ + ln 𝑣 + ln 2 + 𝑣 2 = ln 𝑐
2
4
4
4ln π‘₯ + 2 ln 𝑣 + ln 2 + 𝑣 2 = ln 𝑐
1 + 𝑣 2 = 𝐴 2 + 𝑣 2 + 𝐡𝑣 + 2𝑣 2 𝐢
1
2𝐴 = 1
𝐴=
2
𝐡=0
1
𝐢=
𝐴 + 2𝐢 = 1
4
4
2
2
π‘₯ 𝑣 2+𝑣 =𝑐
π‘₯4
𝑦
π‘₯
2
𝑦
2+
π‘₯
2
=𝑐
𝑦 2 2π‘₯ 2 + 𝑦 2 = 𝑐
Example 3 ( ref i pp. 73)
Solve
π‘₯ 2 + 𝑦 2 𝑑π‘₯ + π‘₯ 2 − π‘₯𝑦 𝑑𝑦 = 0
Solution:
𝑦 = 𝑣π‘₯
π‘₯ 2 + 𝑣π‘₯
2
2
𝑑𝑦 = 𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣
𝑑π‘₯ + π‘₯ 2 − π‘₯ 𝑣π‘₯
2
𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣 = 0
2
π‘₯ 1 + 𝑣 𝑑π‘₯ + π‘₯ 1 − 𝑣 𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣 = 0
1 + 𝑣 2 𝑑π‘₯ + 1 − 𝑣 𝑣 𝑑π‘₯ + π‘₯ 𝑑𝑣 = 0
1 + 𝑣 𝑑π‘₯ + 1 − 𝑣 π‘₯ 𝑑𝑣 = 0
𝑑π‘₯
1−𝑣
+
𝑑𝑣 = 0
π‘₯
1+𝑣
𝑑π‘₯
2
+
− 1 𝑑𝑣 = 0
π‘₯
1+𝑣
ln π‘₯ + 2 ln 1 + 𝑣 − 𝑣 = ln 𝑐
π‘₯ 1 + 𝑣 2 𝑒 −𝑣 = 𝑐
𝑦
π‘₯ 1+
π‘₯
π‘₯+𝑦
2
2
𝑦
𝑒−
= 𝑐π‘₯𝑒
π‘₯
𝑦
=𝑐
π‘₯
Example 3 ( ref i pp. 73)
Solve
π‘₯ 2 + 𝑦 2 𝑑π‘₯ + π‘₯ 2 − π‘₯𝑦 𝑑𝑦 = 0
Solution:
π‘₯ = 𝑒𝑦
𝑑π‘₯ = 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒
𝑒𝑦 2 + 𝑦 2 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒 + 𝑒𝑦 2 − 𝑒𝑦 𝑦 𝑑𝑦 = 0
𝑦 2 𝑒2 + 1 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒 + 𝑦 2 𝑒2 − 𝑒 𝑑𝑦 = 0
𝑒2 + 1 𝑒 𝑑𝑦 + 𝑦 𝑑𝑒 + 𝑒2 − 𝑒 𝑑𝑦 = 0
𝑒3 + 𝑒2 𝑑𝑦 + 𝑒2 + 1 𝑦 𝑑𝑒 = 0
𝑑𝑦
𝑒2 + 1
+ 2
𝑑𝑒 = 0
𝑦
𝑒 𝑒+1
𝑑𝑦
1 1
2
+ − + 2+
𝑑𝑒 = 0
𝑦
𝑒 𝑒
𝑒+1
ln 𝑦 − ln 𝑒 − 𝑒−1 + 2 ln 𝑒 + 1 = ln 𝑐
𝑦 𝑒+1
ln
𝑒
2
= ln 𝑐 + 𝑒 −1
𝑒2 + 1
𝐴 𝐡
𝐢
= + 2+
𝑒2 𝑒 + 1
𝑒 𝑒
𝑒+1
𝑒2 + 1 = 𝐴 𝑒2 + 𝑒 + 𝐡 𝑒 + 1 + 𝐢𝑒2
𝐡=1
𝐴+𝐡 =0
𝐴 = −1
𝐴+𝐢 =1
𝐢=2
𝑦 𝑒+1
ln
𝑒
𝑦 𝑒+1
𝑒
π‘₯
𝑦 𝑦+1
π‘₯
𝑦
π‘₯+𝑦
2
2
= ln 𝑐 + 𝑒 −1
2
= 𝑐𝑒 𝑒
−1
2
= 𝑐𝑒
= 𝑐π‘₯𝑒
𝑦
𝑦
π‘₯
π‘₯
π‘₯ = 𝑒𝑦
π‘₯
𝑒=
𝑦
Assignment #3
Exercises 1-21, 23-35 on pp. 28-29 of ref ii
Example 1 ( ref ii pp. 32)
Solution:
𝑀 = 3π‘₯ 2 𝑦 − 6π‘₯
𝑁 = π‘₯ 3 + 2𝑦
πœ•π‘€
= 3π‘₯ 2
πœ•π‘¦
πœ•π‘
= 3π‘₯ 2
πœ•π‘₯
πœ•πΉ
= 3π‘₯ 2 𝑦 − 6π‘₯
πœ•π‘₯
𝐹=
π‘₯ 3𝑦
−
3π‘₯ 2
+𝑔 𝑦
𝑔′ 𝑦 = 2𝑦
πœ•π‘€ πœ•π‘
=
πœ•π‘¦
πœ•π‘₯
πœ•πΉ
= π‘₯ 3 + 𝑔′ 𝑦 = 𝑁
πœ•π‘¦
π‘₯3
+ 𝑔′ 𝑦 =
π‘₯3
+ 2𝑦
𝑔 𝑦 = 𝑦2
𝐹 = π‘₯ 3 𝑦 − 3π‘₯ 2 + 𝑦 2
π‘₯ 3 𝑦 − 3π‘₯ 2 + 𝑦 2 = 𝑐
Example 2 ( ref ii pp. 33)
Solution:
𝑀 = 2π‘₯ 3 − π‘₯𝑦 2 − 2𝑦 + 3
𝑁 = −π‘₯ 2 𝑦 − 2π‘₯
πœ•π‘€
= −2π‘₯𝑦 − 2
πœ•π‘¦
πœ•π‘
= −2π‘₯𝑦 − 2
πœ•π‘₯
πœ•π‘€ πœ•π‘
=
πœ•π‘¦
πœ•π‘₯
πœ•πΉ
= −π‘₯ 2 𝑦 − 2π‘₯
πœ•π‘¦
1
𝐹 = − π‘₯ 2 𝑦 2 − 2π‘₯𝑦 + β„Ž π‘₯
2
πœ•πΉ
= −π‘₯𝑦 2 − 2𝑦 + β„Ž′ π‘₯
πœ•π‘₯
−π‘₯𝑦 2 − 2𝑦 + β„Ž′ π‘₯ = 2π‘₯ 3 − π‘₯𝑦 2 − 2𝑦 + 3
β„Ž′ π‘₯ = 2π‘₯ 3 + 3
1 4
β„Ž π‘₯ = π‘₯ + 3π‘₯
2
1
1
𝐹 = π‘₯ 4 + 3π‘₯ − π‘₯ 2 𝑦 2 − 2π‘₯𝑦
2
2
1 4
1
𝑐
π‘₯ + 3π‘₯ − π‘₯ 2 𝑦 2 − 2π‘₯𝑦 =
2
2
2
π‘₯ 4 + 6π‘₯ − π‘₯ 2 𝑦 2 − 4π‘₯𝑦 = 𝑐
Example 3 ( ref iii pp. 22)
Solution:
𝑀 = cos π‘₯ + 𝑦
𝑁 = 3𝑦 2 + 2𝑦 + cos π‘₯ + 𝑦
πœ•π‘€
= − sin π‘₯ + 𝑦
πœ•π‘¦
πœ•π‘
= − sin π‘₯ + 𝑦
πœ•π‘₯
πœ•π‘€ πœ•π‘
=
πœ•π‘¦
πœ•π‘₯
πœ•πΉ
= cos π‘₯ + 𝑦
πœ•π‘₯
𝐹 = sin π‘₯ + 𝑦 + 𝑔 𝑦
𝐹 = sin π‘₯ + 𝑦 + 𝑦 3 + 𝑦 2
πœ•πΉ
= cos π‘₯ + 𝑦 + 𝑔′ 𝑦
πœ•π‘¦
sin π‘₯ + 𝑦 + 𝑦 3 + 𝑦 2 = 𝑐
𝑔′ 𝑦 = 3𝑦 2 + 2𝑦
𝑔 𝑦 = 𝑦3 + 𝑦2
Example 4 ( ref iii pp. 23)
Solution:
𝑀 = cos 𝑦 sinh π‘₯ + 1
𝑁 = − sin 𝑦 cosh π‘₯
πœ•π‘€
= − sin 𝑦 sinh π‘₯
πœ•π‘¦
πœ•π‘€ πœ•π‘
=
πœ•π‘¦
πœ•π‘₯
πœ•π‘
= − sin 𝑦 sinh π‘₯
πœ•π‘₯
πœ•πΉ
= − sin 𝑦 cosh π‘₯
πœ•π‘¦
𝐹 = cos 𝑦 cosh π‘₯ + β„Ž π‘₯
πœ•πΉ
= cos 𝑦 sinh π‘₯ + β„Ž′ π‘₯
πœ•π‘₯
β„Ž′ π‘₯ = 1
β„Ž π‘₯ =π‘₯
𝐹 = cos 𝑦 cosh π‘₯ + π‘₯
cos 𝑦 cosh π‘₯ + π‘₯ = 𝑐
@ π‘₯ = 1, 𝑦 = 2
𝑐 =0.358
cos 𝑦 cosh π‘₯ + π‘₯ = 0.358
Example 5 ( ref iv pp. 94)
Solution:
𝑀 = 2π‘₯ + 𝑦 2
𝑁 = 2π‘₯𝑦
πœ•π‘€
= 2𝑦
πœ•π‘¦
πœ•π‘
= 2𝑦
πœ•π‘₯
πœ•π‘€ πœ•π‘
=
πœ•π‘¦
πœ•π‘₯
πœ•πΉ
= 2π‘₯𝑦
πœ•π‘¦
𝐹 = π‘₯𝑦 2 + π‘₯ 2
𝐹 = π‘₯𝑦 2 + β„Ž π‘₯
π‘₯𝑦 2 + π‘₯ 2 = 𝑐
πœ•πΉ
= 𝑦 2 + β„Ž′ π‘₯
πœ•π‘₯
β„Ž′ π‘₯ = 2π‘₯
β„Ž π‘₯ = π‘₯2
Example 6 ( ref iv pp. 97)
Solution:
𝑀 = 𝑦 cos π‘₯ + 2π‘₯𝑒 𝑦
𝑁 = sin π‘₯ + π‘₯ 2 𝑒 𝑦 − 1
πœ•π‘€
= cos π‘₯ + 2π‘₯𝑒 𝑦
πœ•π‘¦
πœ•π‘€ πœ•π‘
=
πœ•π‘¦
πœ•π‘₯
πœ•πΉ
= 𝑦 cos π‘₯ + 2π‘₯𝑒 𝑦
πœ•π‘₯
πœ•π‘
= cos π‘₯ + 2π‘₯𝑒 𝑦
πœ•π‘₯
𝐹 = 𝑦 sin π‘₯ + π‘₯ 2 𝑒 𝑦 + 𝑔 𝑦
πœ•πΉ
= sin π‘₯ + π‘₯ 2 𝑒 𝑦 + 𝑔′ 𝑦
πœ•π‘¦
𝑔′ 𝑦 = −1
𝑔 𝑦 = −𝑦
𝐹 = 𝑦 sin π‘₯ + π‘₯ 2 𝑒 𝑦 − 𝑦
𝑦 sin π‘₯ + π‘₯ 2 𝑒 𝑦 − 𝑦 = 𝑐
Example 1 ( ref ii pp. 32)
Solution:
𝑀 = 3π‘₯ 2 𝑦 − 6π‘₯
𝑁 = π‘₯ 3 + 2𝑦
πœ•πΉ
= 3π‘₯ 2 𝑦 − 6π‘₯
πœ•π‘₯
𝐹 = π‘₯ 3 𝑦 − 3π‘₯ 2 + 𝑔 𝑦
πœ•πΉ
= π‘₯ 3 + 2𝑦
πœ•π‘¦
𝐹 = π‘₯ 3𝑦 + 𝑦 2 + β„Ž π‘₯
𝑔 𝑦 = 𝑦2
β„Ž π‘₯ = −3π‘₯ 2
𝐹 = π‘₯ 3 𝑦 − 3π‘₯ 2 + 𝑦 2
π‘₯ 3 𝑦 − 3π‘₯ 2 + 𝑦 2 = 𝑐
Example 2 ( ref ii pp. 33)
Solution:
𝑀 = 2π‘₯ 3 − π‘₯𝑦 2 − 2𝑦 + 3
𝑁 = −π‘₯ 2 𝑦 − 2π‘₯
πœ•πΉ
= 2π‘₯ 3 − π‘₯𝑦 2 − 2𝑦 + 3
πœ•π‘₯
1
1
𝐹 = π‘₯ 4 − π‘₯ 2 𝑦 2 + 2π‘₯𝑦 + 3π‘₯ + 𝑔 𝑦
2
2
πœ•πΉ
= −π‘₯ 2 𝑦 − 2π‘₯
πœ•π‘¦
1 2 2
𝐹 = − π‘₯ 𝑦 − 2π‘₯𝑦 + β„Ž π‘₯
2
1
β„Ž π‘₯ = π‘₯ 4 + 3π‘₯
2
𝑔 𝑦 =0
1 4 1 2 2
π‘₯ − π‘₯ 𝑦 + 2π‘₯𝑦 + 3π‘₯ + 𝑔 𝑦
2
2
1 4 1 2 2
𝑐
π‘₯ − π‘₯ 𝑦 + 2π‘₯𝑦 + 3π‘₯ =
2
2
2
𝐹=
π‘₯ 4 + 6π‘₯ − π‘₯ 2 𝑦 2 − 4π‘₯𝑦 = 𝑐
Download